Le rôle des prépositions : le cas de FOR - Philippe Rapatel (Anglophonia)
The purpose of this paper is to analyse the role of prepositions. This role, at first, is to introduce a subordinate element and to determine its syntactic function. The subordinate element is the prepositional phrase but, since everybody does not agree on that term, confusions result from this terminology issue. The complement to the preposition has, as its function, to be the locator of the element it is related to via the preposition. Anchoring is an essential operation in this relation.Preposition FOR plays a felicitous part in this matter since it fills in the interval pointed to by its presence between the locator and the located term. We will see to what extent the function of FOR can be applied to all the utterances where it appears as a preposition.